A possible explanation of the 'exchange rate disconnect puzzle': A common solution to three major macroeconomic puzzles? - Charles Yuji Horioka; Nicholas Ford (Osaka University, Institute of Social and Economic Research (ISER), 2016)
Meese and Rogoff (1983) and subsequent studies find that economic fundamentals are apparently not able to explain exchange rate movements, but we argue that this so-called "Exchange Rate Disconnect Puzzle" arose because researchers such as Meese and Rogoff (1983) did not use the right fundamentals and because they did not allow for the forward-looking nature of exchange rate determination. Further, because they apparently were not aware that financial markets by themselves could not equalise interest rates across countries, they did not properly appreciate that the exchange rate is strongly influenced by agents' expectations of aggregated differences in local returns. Thus, we believe that the same underlying explanation provided by Ford (2015) and Ford and Horioka (2016a and 2016b) for the Feldstein-Horioka (1980) Puzzle and the PPP Puzzle - namely that financial markets alone cannot achieve net transfers of financial capital and cannot equalise real interest rates across countries - also helps explain why previous attempts to connect changes in the exchange rate to economic fundamentals have not been successful, and so can also be said to contribute to solving the Exchange Rate Disconnect Puzzle.
Keywords: F21; F31; F32; F36; G15; 330; Exchange Rate Disconnect Puzzle; exchange rate determination; exchange rate volatility; Feldstein-Horioka puzzle or paradox; financial market integration; goods market integration; international capital flows; international capital mobility; net transfers of capital; PPP puzzle; purchasing power parity puzzle; real interest rate equalisation; real interest rate parity